2020
DOI: 10.1002/hbm.25036
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic functional connectivity between nucleus accumbens and the central executive network relates to chronic cannabis use

Abstract: The neural mechanisms of drug cue‐reactivity regarding the temporal fluctuations of functional connectivity, namely the dynamic connectivity, are sparsely studied. Quantifying the task‐modulated variability in dynamic functional connectivity at cue exposure can aid the understanding. We analyzed changes in dynamic connectivity in 54 adult cannabis users and 90 controls during a cannabis cue exposure task. The variability was measured as standard deviation in the (a) connectivity weights of the default mode, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 142 publications
0
7
0
Order By: Relevance
“…A total of 18 studies were included in this review (Bitter et al 2014 ; Charboneau et al 2013 ; Cousijn et al 2013 ; de Sousa Fernandes Perna et al 2017 ; Feldstein Ewing and Chung 2013 ; Filbey and Dunlop 2014 ; Filbey et al 2016 ; Filbey et al 2009 ; Goldman et al 2013 ; Karoly et al 2019 ; Kleinhans et al 2020 ; Kuhns et al 2020 ; Vingerhoets et al 2016 ; Wetherill et al 2014 ; Wetherill et al 2016 ; Wetherill et al 2015 ; Yoo et al 2020 ; Zhou et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 18 studies were included in this review (Bitter et al 2014 ; Charboneau et al 2013 ; Cousijn et al 2013 ; de Sousa Fernandes Perna et al 2017 ; Feldstein Ewing and Chung 2013 ; Filbey and Dunlop 2014 ; Filbey et al 2016 ; Filbey et al 2009 ; Goldman et al 2013 ; Karoly et al 2019 ; Kleinhans et al 2020 ; Kuhns et al 2020 ; Vingerhoets et al 2016 ; Wetherill et al 2014 ; Wetherill et al 2016 ; Wetherill et al 2015 ; Yoo et al 2020 ; Zhou et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…We extracted brain function during exposure to CAN vs NEU stimuli, in the following groups: (i) within cannabis users in 12 out of 18 studies (Charboneau et al 2013 ; Cousijn et al 2013 ; de Sousa Fernandes Perna et al 2017 ; Feldstein Ewing et al 2013 ; Filbey et al 2009 ; Filbey and Dunlop 2014 ; Filbey et al 2016 ; Goldman et al 2013 ; Karoly et al 2019 ; Kleinhans et al 2020 ; Wetherill et al 2014 ; Wetherill et al 2015 ) and (ii) between cannabis users and non-using controls in eight studies (Bitter et al 2014 ; Cousijn et al 2013 ; de Sousa Fernandes Perna et al 2017 ; Filbey et al 2016 ; Kleinhans et al 2020 ; Kuhns et al 2020 ; Yoo et al 2020 ; Zhou et al 2019 ). We additionally extracted brain function during exposure to CAN vs NEU stimuli between distinct cannabis subgroups, which was reported in 1–2 studies: dependent vs non-dependent users (2 studies) (Filbey and Dunlop 2014 ; Zhou et al 2019 ); high vs low problem cannabis use (2 studies) (Cousijn et al 2013 ; Vingerhoets et al 2016 ); early vs late cannabis use onset (1 study) (Cousijn et al 2013 ; Wetherill et al 2016 , frequent vs sporadic ( n = 1); cannabis use only vs cannabis and tobacco use (Kuhns et al 2020 ); and male vs female cannabis users (1 study) (Wetherill et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, excessively increased temporal variability of FC during rest has been reported in multiple diseases including schizophrenia ( 28 ), major depressive disorder ( 29 ), bipolar disorder ( 30 ), and autism spectrum disorder ( 67 ), potentially reflecting a under-constrained brain network and disrupted information exchanges among brain systems ( 26 , 31 , 35 ). Interestingly, some other recent studies have reported that the uses of alcohol ( 31 ), nicotine ( 32 ), and cannabis ( 33 ) are all related to an increased temporal variability of functional brain network. Combining these previous findings with our results, it may be considered that increased temporal variability of FC is a common hallmark underlying the development of multiple substance use disorders including BQ dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the “dynamic FC” has become a new hot spot in neuroimaging studies, which have been associated with learning ( 23 ), cognition ( 24 ), emotion ( 25 ), personality traits ( 26 , 27 ), as well as common psychiatric diseases including schizophrenia ( 28 ), major depressive disorder ( 29 ) and bipolar disorder ( 30 ). In particular, it was suggested that using addictive substances such as alcohol ( 31 ), nicotine ( 32 ), cannabis ( 33 ), and cocaine ( 34 ) could alter the dynamic FC patterns. For example, it was found that patients with alcohol use disorder exhibited significantly higher temporal variability of FC between the cerebellum and both the frontoparietal and ventral attention networks ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been convincing evidence that brain dynamics rest on the orchestrated activity of several networks of brain regions which transition in recurring patterns over time (Alexandrov 1999; Meer et al 2020). These transitions between brain networks have been associated with to cognition and (ab)normal behaviour (Engel et al 2001; Thompson et al 2013; Vidaurre et al 2017; Liégeois et al 2019; Lurie et al 2020; Yoo et al 2020). However, a fundamental question remains, namly at which particular spatiotemporal scale the whole-brain functional networks are able to optimally transition.…”
Section: Introductionmentioning
confidence: 99%